Bimodal intensity-modulated radiotherapy in combination with carbon ion therapy (C12) of mucosal melanomas - data of the last decade from Heidelberg University Hospital - Bauer, Lukas; Paul, Angela; Regnery, Sebastian; Deng, Maximilian Y.; Ellerbrock, Malte; Mielke, Thomas; Harrabi, Semi B.; Seidensaal, Katharina; Held, Thomas; Herfarth, Klaus; Debus, Jürgen; Hassel, Jessica C.; et al. (Frontiers in Oncology, 2024)
IntroductionDue to the rarity of mucosal melanomas, few recent studies can be found investigating the success and side effects of therapy for this entity with large numbers of patients. In this retrospective analysis, the efficacy and toxicity of combined intensity-modulated radiotherapy (IMRT) and carbon ion therapy (C12) of mucosal melanomas were analyzed to contribute to a better understanding of this rare disease.MethodsTwenty-two patients were included from 2013 to 2022 in the Department of Radiation Oncology at Heidelberg University Hospital. 19 patients received bimodal radiotherapy consisting of radiotherapy by IMRT and carbon ion therapy (C12). 3 patients received photon only IMRT. In addition to Overall Survival (OS), local control rate (LCR), locoregional control rate (LRCR) and progression-free survival (PFS), early and late toxicity of treatment was analyzed. Bimodal radiotherapy consisted of IMRT of the primary tumor region and cervical lymph nodes in a single dose of 2 Gy up to the dose of 50.0 Gy in the basic schedule after application of a C12 boost of the primary tumor region up to 24 Gy (RBE) in a single dose of 3 Gy (RBE) up to the total dose of 74.0 Gy (RBE) in 5-6 fractions/week. Photon only radiotherapy comprised IMRT up to total doses of 66-70,4 Gy in 5 fractions/week.ResultsAfter 2 years, overall survival, progression-free survival, local control and locoregional control were 46%, 41%, 77% and 77%, respectively. 4 out of 5 patients with local relapse showed in-field recurrence inside the C12 boost volume. The primary tumor in these patients was always located in the main nasal cavity and/or paranasal sinus. Leading acute toxicity was grade 2 mucositis (12 patients, 55%) followed by grade 1 radiation dermatitis (10 patients, 45%). The cumulative incidence of late grade 3 toxicities was 15%.DiscussionThe combination of IMRT with carbon ion therapy in the treatment of mucosal melanoma provides promising local control rates with mild acute toxicity despite unfavorable patient preselection. The unfavorable overall survival as well as progression-free survival rates indicate that concomitant systemic therapies should be the subject of future research.